Effect of magnetic powder on membrane fouling mitigation and microbial community/composition in membrane bioreactors (MBRs) for municipal wastewater treatment. (February 2018) - Liu, Yi; Liu, Qiang; Li, Jixiang; Ngo, Huu Hao; Guo, Wenshan; Hu, Jiajun; Gao, Min-tian; Wang, Qiyuan; Hou, Yuansheng
Graphical abstract: Highlights: Addition of magnetic powder prolonged MBR's operating time from 28 days to 48 days. Both bioflocculation and adsorption only slightly reduce membrane fouling. Magnetic bio-effect is the main factor to mitigate membrane fouling. Less amount of SMP and macromolecules in the MAS-MBR were observed. The enrichment of pioneer bacteria from bulk sludge might cause severe fouling. Abstract: This study aims to investigate the usefulness of magnetic powder addition in membrane bioreactors (MBRs) for membrane fouling mitigation and its effect on microbial community and composition. The comparison between the two MBRs (one with magnetic powder (MAS-MBR) and one without magnetic powder (C-MBR)) was carried out to treat synthetic municipal wastewater. Results showed that bioflocculation and adsorption of magnetic powder contributed only minimally to membrane fouling mitigation while the slower fouling rate might be ascribed to magnetic bio-effect. The macromolecules (larger than 500 kDa and 300–500 kDa) of soluble microbial product from the MAS-MBR were reduced by 24.06% and 11.11%, respectively. High-throughput sequencing demonstrated the most abundant genera of biofilm sludge indicated lower abundance in bulk sludge from the MAS-MBR compared to the C-MBR. It is possible that less membrane fouling is connected to reductions in large molecules and pioneer bacteria from bulk sludge.